"A Meeting of Minds": Using Clickers for Critical Thinking and Discussion in Large Sociology Classes - Mollborn, Stefanie; Hoekstra, Angel (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Because lecture-based teaching limits student learning, many instructors are interested in pedagogical strategies that support critical thinking, student participation, and group discussion in large classrooms. Audience response systems, or "clickers," are an emerging tool for addressing this problem, but predominant pedagogical models for clicker use developed in the natural sciences often do not encourage the "inquiry-guided learning" that is useful in sociology. This article introduces readers to clicker technology and outlines a new pedagogical model for clicker use designed to address sociological learning goals, including critical thinking, applications of concepts to real-life experiences, and critiques of sociological methods. The authors discuss the effects of clickers for classroom interaction and students’ experiences in three undergraduate sociology courses, using quantitative and qualitative data about students’ perceptions of the effects of this pedagogical model on learning. The results suggest that the model positively affects participation, critical thinking, and classroom interaction dynamics. The authors conclude with practical suggestions for instructors considering implementing clickers in sociology courses.